Nikah Bawah Tangan Dan Itsbat Nikah - Abd. Basit Misbachul Fitri; In'am Fauzi; Abdul Wahid Azza (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
According to Law no. 1 of 1974, Marriage is a spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the belief in God Almighty. Underhand marriage is a marriage that is carried out in secret without being attended by anyone except those who are getting married. In Indonesia it is called a sirri marriage, meaning veiled, closed, silent, private. This marriage is hidden from the public, and is not registered at the authorized institution. Marriage under the hand is legal according to religion only (if the conditions and pillars have been fulfilled), but does not get legal legality from the state. The Indonesian Ulema Council (MUI) in 1980 issued a fatwa: "Marriage under the hand is valid because the conditions and pillars of marriage have been fulfilled, but it is unlawful if there are madharats. Marriage must be officially registered with the competent authority, as a preventive measure to prevent negative impacts/madharat (syadd li al-dzari'ah)." Marriage under the hand has an impact or legal consequences that are detrimental to the husband and especially the wife and children, both psychologically, administratively, hereditary, economically, and even religion, the harm is greater than the benefit. This marriage can be resolved by submitting an application for a marriage determination (Itsbat Nikah) at the Religious Court through a trial process by fulfilling the juridical requirements. Itsbat nikah aims to create order in marriage in society which has implications for protecting the rights of whoever related in marriage.